Studies on the Response of Phosphate Fertilized Green Manure Legumes Intertilled with Maize on Succeeding Wheat - Shukla, S.C.; Sinha, R. (Journal of Soil and Water Conservation, 2022)
In India, specially the northern part, the practice of growing cereal after cereal is in vogue from years immemorial. There can be no dispute that this practice is not based on perfect planning in relation to soil and its fertility. This not only depletes the soil of its inherent fertility status causing gradual reduction in crop yield, but the texture also gets affected. It is being noticed that in the intensive system of cultivation, on the plains, wheat is often taken after maize with the only object of obtaining both these food grains in a year. This type of cropping pattern has a major defect in the depletion of the soil fertility and the status of which can be upheld if it is green manured with a legume as an integral part of it. This has an advan- tage of getting a crop without losing the kharif one